Anti-tumor effect of antibody-drug conjugate targeting cell adhesion molecule 1 on GIST cells representing small intestinal GIST - Makoto Yoshida; Jiayin Yuan; Takako Kihara; Neinei Kimura; Takashi Yamasaki; Mizuka Ohkouchi; Yuka Hashikura; Koji Isozaki; Man Hagiyama; Akihiko Ito; Seiichi Hirota (Elsevier, 2024)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the alimentary tract. The prognosis depends on the primary site, and small intestinal GISTs have a worse prognosis than gastric GISTs. Molecularly targeted drugs to inhibit tyrosine kinase activity of KIT were used for unresectable or recurrent GISTs. However, secondary resistance to the drugs is often acquired, and treatments based on other mechanisms are needed. Previously, we reported that cell adhesion molecule 1 (CADM1) was highly expressed in most of small intestinal GISTs but not in most of gastric GISTs. In the present study, we examined whether the antibody-drug conjugate (ADC) with anti-CADM1 antibody and monomethyl auristatin E (anti-CAD-ADC) shows anti-tumor effect on CADM1-expressing human GIST cells. The ADC adhibited in this study was previously used for CADM1-expressing human mesothelioma cells and showed anti-tumor effect for them in vitro. GIST-T1 cell line of gastric origin which scarcely expresses CADM1 and GIST-T1 cells transfected with CADM1 cDNA (GIST-T1-CAD cells) which highly expresses CADM1 and represents small intestinal GIST were used. In vitro, anti-CAD-ADC showed remarkable cytotoxic activity on GIST-T1-CAD cells, but control ADC did not. Both anti-CAD-ADC and control ADC did not show anti-tumor effect on original GIST-T1 cells. When GIST-T1-CAD cells were subcutaneously injected to the nude mice, intravenous administration of anti-CAD-ADC showed inhibitory effect for tumor enlargement. Tumor of GIST-T1 cells grew even after anti-CAD-ADC injection. When GIST-T1-CAD cells were injected into peritoneal cavity of the SCID mice, intraperitoneal administration of anti-CAD-ADC showed reduction of the peritoneal tumor. On the other hand, peritoneal tumor grew after control ADC administration. Tissue and organ damage due to administration of anti-CAD-ADC was not apparent by macroscopic and histological examinations in mice. These results indicate that anti-CAD-ADC could have apparent anti-tumor effect on CADM1-expressing human GIST cells both in in vitro and in vivo mouse models.